Right Punishment For The Performers Of Corruption - Arya Wibisono; Kunta Dwi Pangestu; Rahul May Kardo Albert. D (Dinasti Research, 2020)
Corruption has been a serious problem since the days of our ancestors until now. Whatever means have been used to prevent this from happening again. But unfortunately the deterrent effect that is felt does not really make the perpetrator repent. Once the perpetrator commits an act of corruption, then once he feels the punishment. Then he does it again or even new seeds of corruption perpetrators emerge. Recently the RKUHP being drafted by the DPR has drawn a lot of criticism. How could I not, instead of creating fear and a deterrent effect, this RKUHP actually eases the punishment for corruptors. The RKUHP, which is considered to be inconsistent with the existing laws, has caused confusion among law enforcers. Weakening the side of punishments suchas fines and prison terms for corruptors will lead to more rampant corruption cases. The purpose of writing this article is to analyze what kind of punishment we have applied and assess whether the punishment is appropriate to be applied or there are still many shortcomings. Then in compiling this article the writing method used is descriptive qualitative with the data source used by the author, namely the research library, which is data obtained from existing literature from books, journals, the internet and other references that are in accordance with the research problem. Eradicating corruption from above through the KPK without any reinforcement by including provisions from the United Nation Convention Against Corruption (UNCAC), such as an eagle preying on rats in a bottle of bars. Because so far, the Corruption Act has not met all the standards of the UNCAC.